METAPHOR'S FUNCTION IN THE SYSTEM OF STYLISTIC TECHNIQUES - KarjawbaevOrazaliEsbosinuli; Toleubayeva A.O (Western European Studies, 2024)
Given the parallelism of the two conceptual aspects, it is generally known that in stylistics, metaphor expresses the link between subject-logical meaning and contextual meaning. When one object is applied to another, a key characteristic of the second object is revealed. This is known as a covert analogy, or metaphor. Many linguists believe that metaphor, one of the most often used and encountered linguistic tropes, is the most crucial tool. The concept of metaphor is so unique to poetic language that it is occasionally used as a synonym for verbal imagery. The words employed in a metaphor have a figurative meaning rather than a literal one. Metaphorical language frequently refers to "figurative" or "sign" language
Keywords: Metaphor; theory of metaphor; political language; literary language